Beberapa sediaan tablet yang telah dimodifikasi dengan metode yang dapat meningkatkan kelarutan - Sari, Aulia Permata; Rahmah, Azka Nurkhairiyah; Nurholisa, Neng Dera Siti; Andriani, Febby; Pahlevi, Muhamad Reza; Sutoro, Meylani (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2024)
Nowadays there are many pharmaceutical preparations, one of which is tablet preparation. Tablets are solid preparations containing medicinal ingredients with or without fillers. Modified preparation means that the pharmaceutical formulation has been changed from the standard or original formulation. Modification can be done for several purposes, such as increasing solubility, increasing bioavailability, regulating drug release, increasing stability, or improving other formulation properties. The purpose of this paper is to provide a perspective on the methods used to improve drug solubility, dissolution rate, and stability of active substances. The writing of this review article uses the research journal literature study method. The primary sources used have been published online through Google scholar by entering the keywords modified active substance, solid dispersion, tablet making methods that increase solubility, tablet dissolution. In this review, it was found that there are techniques that can be done such as co-amorphous, co-crystalline, nanoemulsifying, micronization, precipitation, melting, addition of crushing agents and factorial methods of adding binders to be the choice of scientists in developing pharmaceutical preparations with active ingredients that have poor BCS values.